Cryptic promoter activation occurs by at least two different mechanisms in the Arabidopsis genome. (2nd August 2021) - Kudo, Hisayuki; Matsuo, Mitsuhiro; Satoh, Soichirou; Hata, Takayuki; Hachisu, Rei; Nakamura, Masayuki; Yamamoto, Yoshiharu Y.; Kimura, Hiroshi; Matsui, Minami; Obokata, Junichi
SUMMARY: In gene‐trap screening of plant genomes, promoterless reporter constructs are often expressed without trapping of annotated gene promoters. The molecular basis of this phenomenon, which has been interpreted as the trapping of cryptic promoters, is poorly understood. Here, we found that cryptic promoter activation occurs by at least two different mechanisms using Arabidopsis gene‐trap lines in which a firefly luciferase ( LUC ) open reading frame (ORF) without an apparent promoter sequence was expressed from intergenic regions: one mechanism is 'cryptic promoter capturing', in which the LUC ORF captured pre‐existing promoter‐like chromatin marked by H3K4me3 and H2A.Z, and the other is 'promoter de novo origination', in which the promoter chromatin was newly formed near the 5′ end of the inserted LUC ORF. The latter finding raises a question as to how the inserted LUC ORF sequence is involved in this phenomenon. To examine this, we performed a model experiment with chimeric LUC genes in transgenic plants. Using Arabidopsis psaH1 promoter– LUC constructs, we found that the functional core promoter region, where transcription start sites (TSSs) occur, cannot simply be determined by the upstream nor core promoter sequences; rather, its positioning proximal to the inserted LUC ORF sequence was more critical. This result suggests that the insertion of the coding sequence alters the local distribution of TSSs in the plant genome. The possible impact of the two types of cryptic promoter activation mechanisms on plant genome evolution and endosymbiotic gene transfer is discussed. Significance Statement: In promoter‐trap screenings of plant genomes, unexplainable expression of the reporter is occasionally reported. This is hypothesized to be caused by the trapping of enigmatic cryptic promoters. Here we demonstrate that two types of cryptic promoters exist in terms of chromatin remodeling: one is the pre‐existing promoter‐like chromatin whose inherent transcripts are hardly detectable, and the other is the de novo origination of promoter chromatin accompanying reporter insertion.